2019
DOI: 10.1016/j.jff.2019.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Glycated whey proteins protect NOD mice against type 1 diabetes by increasing anti-inflammatory responses and decreasing autoreactivity to self-antigens

Abstract: Our previous studies suggested that early glycation products (EGPs) generated in the first step of Maillard reaction/glycation were anti-inflammatory. The objectives of the present study were to determine the effects of EGPs derived from the whey protein isolate-glucose system on type 1 diabetes (T1D), and the underlying immunological mechanisms. In non-obese diabetic (NOD) mice, EGPs at the physiological dose of 600 mg/kg/day increased glucose metabolism, decreased non-fasting blood glucose levels and T1D inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…No inflammation was observed for anterior and ventral prostates using histopathological analysis (data not shown). In our previous studies, however, H&E staining was shown to be less sensitive than flow cytometric analysis 9 , evidenced by the subtle differences in the immune infiltration of the pancreas being successfully detected using the latter, but not the former. Therefore, the infiltrating immune cells in the anterior prostate, after being treated for 6 months, were analyzed by flow cytometry (Fig 2C).…”
Section: Chronic Exposure To Egps Increases the Survival Rate And Moderately Reduces The Prostatic Inflammationmentioning
confidence: 90%
See 4 more Smart Citations
“…No inflammation was observed for anterior and ventral prostates using histopathological analysis (data not shown). In our previous studies, however, H&E staining was shown to be less sensitive than flow cytometric analysis 9 , evidenced by the subtle differences in the immune infiltration of the pancreas being successfully detected using the latter, but not the former. Therefore, the infiltrating immune cells in the anterior prostate, after being treated for 6 months, were analyzed by flow cytometry (Fig 2C).…”
Section: Chronic Exposure To Egps Increases the Survival Rate And Moderately Reduces The Prostatic Inflammationmentioning
confidence: 90%
“…Age-matched non-diabetic NOD males (approximately 4-month-old) were randomly separated into 2 groups and gavaged daily with NR and EGPs at 600 mg/kg body weight (BW) for up to 6 months. This dose was physiologically relevant as discussed previously 7 , and EGPs at this dose protected NOD mice from developing T1D 9 . Mice were euthanized at month 3 and 6 following the first dosing.…”
Section: Mouse Model Of Autoimmune Prostatitis and The Treatment Regimenmentioning
confidence: 95%
See 3 more Smart Citations